Beyond Traditional Love: The Cultural and Psychological Dilemma of the Phenomenon of Young People Avoiding the New Year and Its Response - Hu, Zhou; Yajun, Fang (Journal of Cultural Analysis and Social Change, 2025)
The phenomenon of young people avoiding the Spring Festival refers to the choice and behavior of some young people to avoid going home for the New Year due to their fear of the pressure of traditional festivals or to avoid being influenced by multiple groups such as parents and relatives and friends. The motives behind the phenomenon of young people avoiding the New Year mainly stem from their avoidance of marital and romantic relationship issues, their escape from their parents' educational expectations, their evasion from peer work comparisons, and their farewell to relatives' social obligations. In terms of their cultural and psychological predicaments, the phenomenon of young people avoiding the New Year is characterized by emotional rifts such as the panic over marriage and love brought about by traditional marriage culture, the expectation pressure internalized by the dragon and phoenix totem culture, the achievement anxiety strengthened by the culture of face survival, and the burden of human relationships maintained by the culture of blood ties and geographical ties. Thus, in order to help young people overcome cultural and psychological predicaments and regain emotional attachment, it is necessary to enhance the emotional identification with free marriage and love and overcome the panic of young people's choices in marriage and love. Promote democratic family education to reduce the pressure on young people to respect and be filial to their parents. Develop moral and friendly relationships to reduce peer anxiety among young people. Establish a correct and rational consumption view and relieve the burden of interpersonal interactions among young people.